2015
DOI: 10.1002/hrm.21651
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Working Mother: Managing Identity and Efficacy Uncertainties During Resocialization

Abstract: The work reentry period following the birth of a first child is a time of uncertainty for a professional woman. During reentry, a new mother is often questioning who she is and how effective she can be as a mother and working professional. In this study, we conceptualize reentry as a period of resocialization as we explore the first‐time mother's changing self‐concept during this time. Specifically, we develop a model that explores the identity and efficacy uncertainties that women experience during resocializ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 68 publications
1
90
1
Order By: Relevance
“…Our multimethod research design enabled us to discover this counterintuitive finding that may not have been discovered if we did not start with a qualitative study. We found that a key to retaining professionally employed new mothers is encouraging their sense of maternal confidence, which differs from previous research that assumes professionally employed new mothers contemplate leaving their jobs due to work demands and an incompatibility between motherhood and work (Buzzanell et al, ; Gatrell, ; Ladge & Greenberg, ). Indeed, the effects of family/parent‐related stressors on work‐related outcomes may be particularly acute for professionally employed women since they often face intense scrutiny by coworkers and may be falsely perceived as less devoted to their career now that they are mothers (Gatrell, ; Meister, Sinclair, & Jehn, in press).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our multimethod research design enabled us to discover this counterintuitive finding that may not have been discovered if we did not start with a qualitative study. We found that a key to retaining professionally employed new mothers is encouraging their sense of maternal confidence, which differs from previous research that assumes professionally employed new mothers contemplate leaving their jobs due to work demands and an incompatibility between motherhood and work (Buzzanell et al, ; Gatrell, ; Ladge & Greenberg, ). Indeed, the effects of family/parent‐related stressors on work‐related outcomes may be particularly acute for professionally employed women since they often face intense scrutiny by coworkers and may be falsely perceived as less devoted to their career now that they are mothers (Gatrell, ; Meister, Sinclair, & Jehn, in press).…”
Section: Discussioncontrasting
confidence: 99%
“…The first author conducted interviews with 40 new mothers who returned to their same employer and professional job following maternity leave. The initial broad objective of these interviews was to learn about the experiences of professionally employed new mothers as they transitioned back to work, an area where little prior empirical research has been conducted (Ladge & Greenberg, ). Through our inductive analytic process, the findings revealed that a woman's confidence in her new maternal role was important to her perceived ability to manage work and family demands and her intent to continue working now that she is a mother.…”
Section: Qualitative Study Of Professionally Employed New Mothersmentioning
confidence: 99%
See 3 more Smart Citations